Aid Memoir - Hollingworth, Larry (Book collections on Project MUSE., 2021)
Mr. Larry's Aid Memoir follows the experiences of Larry Hollingworth, head of UNHCR efforts in Bosnia during the Bosnian conflict of the early to mid 90's. Mr. Hollingworth develops a narrative that traces humanitarian attempts to deliver food and aid to besieged, isolated, and desperate communities throughout the Balkans, including Sarajevo, Banja Luka, and Srebrenica.